A psychometric approach to assess justice perceptions in support of the governance of agricultural sustainability transitions - de Boon, Auvikki; Dressel, Sabrina; Sandström, Camilla; Rose, David Christian (Elsevier, 2023)
There is consensus that we need sustainability transitions and increasing acknowledgement that such transitions should be conducted in a just manner. However, what exactly a ‘just transition’ means and how this should be brought about is less clear. Attempts to examine the justice of transitions to date primarily rely on normative interpretations of what justice means. Using the English agricultural transition as a case, we develop an instrument that builds on the underlying dimensions of justice evaluations to provide a tool for decision-makers to gain insights into societal perceptions of what a just agricultural transition means to them. When adapted, this instrument is also valuable for sustainability transitions in other sectors. We establish adequate construct reliability and validity for a number of constructs such as Equality, Entitlement, and Merit as Principles of Procedural Justice, whilst others such as the different Topics of Distributional Justice will need further refinement.
Keywords: Agriculture; Distributive justice; Procedural justice; Recognitional justice; Sustainable governance; Transitions